The Correlation of Attitudes, Motivation and English Learning Strategies at Senior High School Level in Indramayu City-Wes Java - Uju, Uju; Rukmini, Dwi; Anggani LB, Dwi (English Education Journal, 2019)
This study focuses on exploring the correlation of attitudes, motivation and English learning strategies in an attempt to see wether 1) positive attitudes correlate with motivation, 2) negative attitudes correlate with motivation, 3) positive attitudes correlates with English learning strategies, 4) negative attitudes correlate with English learning strtegies, 5) high motivation correlates with English learning strategies and 6) low motivation correlates with English learning strategies which consequently may provide some pedagogical implications for teachers to benefit in classroom applications. A total of 308 sample were involved in this descriptive study. They were the second grade of senior high school in Indramayu city – West Java. The data were obtained through using two questionnaires; AMTB (SPSS. 21) and SILL (SPSS 21). The results of the two questionnires that for the item 1 (Table 2) is about the awareness of the importance of English and the fact that it shows the good and the poor learners are more aware of this. Subsequent items 2-7 (Table 3 and 4) show the good and poor learners are more interested in learning English and expression of desire to learn English. Next, items 8-10, (Table 5) that they show the actual English interest and effort in learning and improving in an out of the classroom. (the good and poor learners’ positive attitudes correlate with their motivation). However, the first third items (11, 12, and 14), table 6, that the highest rank, the poor learners responses, (.251 **, .414 **, .357 **, agreements) are items related to the difficulty involved in learning English. Moreover, items 5 to 7 (15, 16, 17) study the poor learners find learning English uninteresting and they really find learning English boring. Finally, the low mean scores for items 10 (20), table 8, show that the poor learners do not think that learning English is a waste of time (the poor learners’ negative attitudes do not correlative with their motivation). Furthermore, in line with the strategy, the good learners who have high motivation are more greater than the poor learners who have low motivation (Table 15 and 16). It is highly likely influenced by extrinsic motivation.